Magnetic Resonance Imaging Evaluation of Spinal Tumors and Its Comparison with Histopathological Findings - Saha, Gopal Chandra; Biswas, Prodip Kumar; Rahman, Md Motlabur; Hossain, Mohammed Shahadat; Hossain, Mohammad Zaid; Kabir, AKM Humayon; Alam, Ferdous; Paul, Tushit (Journal of Dhaka Medical College, 2018)
Objective: The objective of the study was to assess the diagnostic usefulness of MRI in evaluation of spinal tumors. Methodology: This cross-sectional study was carried out in Dhaka Medical College Hospital, Dhaka. The data was collected from July 2011 to June 2013 and total 51 patients were included in the study. Data was collected from MRI diagnosed spinal tumors who attended at Radiology and Imaging department of DMCH from OPD and indoor patients. Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of MRI for evaluation of spinal tumors were detected. Results: Out of 51 patients 26 (51%) was intradural extramedullary, 13 (25.5%) was extradural and 12 (23.5%) was intramedullary. Distribution of patients according to MR diagnosis. Among the 51 patients 40 were diagnosed spinal tumor and 11 were not spinal tumor by MRI. Among the 40 spinal tumuor diagnosed 12 (23.5%) were schwannoma, 02 (3.9%) were neuro fibroma, 11(21.6%) were meningioma, 07(13.7%) were ependymoma, 05(9.8%) were astrocytoma, 02(3.9%) were metastasis and 1 (2.0%) was osteoblastoma. Out of all cases 40 were diagnosed as spinal tumour by MRI and among them 39 were confirmed by histopathological evaluation. They were true positive. One case was diagnosed as having spinal tumour by MRI but not confirmed by histopathological findings. That was false positive. Out of 11 cases of non tumour which were confirmed by MRI, 3 were confirmed as spinal tumour and 8 were non-tumour by histopathological findings. They were false negative and true negative respectively. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of the MRI in the diagnosis of spinal tumour were 92.86%, 88.89%, 97.50%, 72.73% and 92.15% respectively. Conclusion: The present study conducted to assess the diagnostic usefulness of MRI in evaluation of spinal tumors among the Bangladeshi population. Study revealed high sensitivity, specificity and accuracy of the MRI in the diagnosis of spinal tumour. MRI should be the initial procedure in the evaluation of suspected tumors of the spine. J Dhaka Medical College, Vol. 26, No.2, October, 2017, Page 162-166